PENGARUH KUALITAS PEMERIKSAAN KEHAMILAN OLEH BIDAN TERHADAP KEPUASAN IBU HAMIL DI PUSKESMAS BRANGSONG I KABUPATEN KENDAL - Rahayu, Sri; Indiati, Resqi (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
In implementing the effort of Sustainable Development Goals in 2030 which is described to achieve gender equality and empower mothers and women and ensure access to affordable, reliable, sustainable and modern energy sources for all people, quality pregnancy screening services are provided during pregnancy. Appropriate backgroundand problem research purposes to determine the effect pregnancy examination on maternity satisfaction. Method this research is observational research, using analytic survey approach. Sampling technique using non probalitity sampling and sampling method using accidental sampling of pregnant women who come to puskesmas brangsong I. Characteristic of pregnant women respondent with junior high school education, work as housewife and income of 0 – 500 thousand rupiah and for quality of reliability, quality of responsiveness, quality of guarantee, quality af attention and quality of responsiveness, quality of guarantee, quality of attention and quality of facilities are obtained enough until very high coefficient, only less on reliability and responsiveness. On satisfaction, it got satisfied with the service given by midwife of brangsong I health center. For the result of regression, quality of pregnancy examination has an effect on satisfaction of pregnant mother. Examination of pregnancy examination has effect on satisfaction of pregnant women at puskesmas of Brangsong I Keywords: examination of pregnancy, quality and satisfaction